Cell Cycle Regulators and Lineage-Specific Therapeutic Targets for Cushing Disease - Araki, Takako; Liu, Ning-Ai (Frontiers in Endocrinology, 2018)
Cell cycle proteins are critical to pituitary development, but their contribution to lineage-specific tumorigenesis has not been well elucidated. Emerging evidence from in vitro human tumor analysis and transgenic mouse models indicates that G1/S-related cell cycle proteins, particularly cyclin E, p27, Rb, and E2F1, drive molecular mechanisms that underlie corticotroph-specific differentiation and development of Cushing disease. The aim of this review is to summarize the literature and discuss the complex role of cell cycle regulation in Cushing disease, with a focus on identifying potential targets for therapeutic intervention in patients with these tumors.